2012
DOI: 10.1177/070674371205701211
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Treatment Response in Major Depressive Disorder: The Impact of Early Symptomatic Improvement

Abstract: Objective: Antidepressants (ADs) are the mainstay of treatment for major depressive disorder (MDD). Despite their widespread usage, a consensus does not exist as to the timing of clinically significant symptomatic improvement during an AD trial. The objective of this review is to provide practitioners with empirically based recommendations pertaining to the optimal duration of index (initial) AD therapy before a clinical intervention is warranted. Methods:We conducted a nonsystematic review, using a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…However, the duration of time before treatment adjustment was longer than recommended: 6 weeks for the TRD group and 8 weeks for the non-TRD group. Current evidence suggests making a change if there is no improvement after 4 to 6 weeks 58. This is due to findings that lack of early improvement is predictive of nonresponse 59,60…”
Section: Discussionmentioning
confidence: 99%
“…However, the duration of time before treatment adjustment was longer than recommended: 6 weeks for the TRD group and 8 weeks for the non-TRD group. Current evidence suggests making a change if there is no improvement after 4 to 6 weeks 58. This is due to findings that lack of early improvement is predictive of nonresponse 59,60…”
Section: Discussionmentioning
confidence: 99%
“…insomnia) are prone to improve or worsen early in treatment as a consequence of side effects of the antidepressant, and hence will confound the assessment of early improvement. There is also some evidence that certain depressive symptoms may improve earlier and to a greater extent than other core symptoms [11,15,29]. Further research into new clinical metrics, possessing greater item sensitivity and specificity for detection of these early effects of antidepressant therapy, is required.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Evidence derived from older antidepressant studies suggested a delayed onset of therapeutic response [6][7][8][9], leading to the conventional belief that patients need to wait at least 8 weeks before concluding whether or not they are responding to an antidepressant [10]. However, recent reviews [10,11] have summarized the many subsequent studies that showed an early onset (within 1-2 weeks) of antidepressant effects in ultimate responders, thereby contradicting the delayed-onset hypothesis and suggesting that responders can be identified earlier in the course of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A double blind, placebo controlled study of elderly outpatients found that those who showed early response, based on a 20% or greater decrease in the 21-item Hamilton Rating Scale for Depression (HAM-D21), in weeks 1, 2 or 3, were more likely to respond well by week 6 [21]. A 2012 nonsystematic review of antidepressant studies in depressed subjects concluded that, whereas outcomes in major depression are heterogeneous, people who respond partially in the first three weeks are more likely to respond more fully later on [22].…”
Section: Delayed Effects Of Antidepressants 469mentioning
confidence: 98%